Ultrafast F2− photodissociation by intense laser pulses: a time-resolved fragment imaging study - Shahi Abhishek; Albeck Yishai; Strasser Daniel (EPJ Web of Conferences, 2019)
We present time-resolved coincidence imaging of F2− photodissociation by 400nm and intense 800nm ultrafast pulses. Coincidence fragment imaging reveals parallel and perpendicular single photon dissociation on 2Σg+ and 2πg states, and additional intense-field dissociation features.